Potret anak stunting usia 2-5 tahun - Fafo, Indri Janisari; Davidson, Sarah Melati; Tauho, Kristiani Desimina (Poltekkes Kemenkes Kupang, 2023)
Introduction: Stunting in Indonesia ranks fifth largest in the world. East Nusa Tenggara is one of the provinces with a high Stunting prevalence of 42.6%. South Central Timor District has the highest number of Stunting cases at 56%, which is higher than national average. Stunting is a chronic condition where the growth and development of children is stunted due to long-term malnutrition. Objective: The purpose of this study is to describe the characteristics of stunted children in terms of breastfeeding history, nutritional status based on weight-for-age score, and frequency of illnesses. Method: The research was conducted using a descriptive survey with a cross-sectional design. Primary data was collected through interviews using a questionnaire. Data was analyzed using univariate analysis to obtain a frequency distribution. Result: The results showed that respondents' characteristics were based on children aged between 24-47 months, the majority of whom were male, and the parents of stunted children had low education levels less than high school, and some were employed. 41.7% of children did not receive exclusive breastfeeding, 94.4% of children did not receive colostrum, 41.7% of children had been given complementary feeding ≤ 6 months, and 88.9% of children had been given prelacteal foods. Most children did not receive breast milk until the age of 2 years, even though all children had received Vitamin A. 63.9% of stunted children also had poor nutritional status and all of them had experienced illnesses in the last 3 months. The government needs to intensify Stunting prevention programs as early as possible.